Government Policies in Addressing Land Subsidence Dynamics in Tambakrejo Semarang - Atha Difa Saputri*; Angel Maris Linda (Riwayat: Educational Journal of History and Humanities, 2023)
Annual land subsidence in Tambakrejo Semarang has decreased by 10 to 13 centimeters. However, the government has not adopted any meaningful policies. This article aims to investigate how many government policy measures have been implemented to address land subsidence in Tambakrejo, Semarang. This article is thus written using an empirical   judicial method in which the researchers do direct field observations, interview informants, and collect data from numerous journals. The results acquired and the impact on the Tambakrejo community of material and immaterial losses caused by subsidence. The government's policies have been implemented, however they have been less effective for the people of Tambakrejo.